Exploring the stress among students during online distance learning: an integration of statistical approach and fuzzy analysis/ Sharifah Fatimatuzzahra Syed Hasnol Hisham ... [et al.] - Syed Hasnol Hisham, Sharifah Fatimatuzzahra; Hassanuddin, Nor Aini; Ahmad, Noraini; Abdullah, Nur Solihah Khadhiah; Jaafar, Ruhana (Universiti Teknologi MARA, Perak, 2022)
ducation is one of the most affected sectors due to COVID-19 that forced online distance learning to be implemented during the pandemic. However, most students are still coping and struggling with this new method of learning. Hence, the stress and depression arise, consequently affect the student's performances. This is a quantitative research study that was carried out using a structured online survey and a random sample approach. 100 students from UiTM Terengganu, Malaysia are selected for the research sample. A 21-item online survey was used in the bquantitative technique to incorporate student stress in online distance learning (ODL). Descriptive analysis is carried out to gauge the student's perception of the challenges that they faced in this type of learning. In this research, the Fuzzy Analytic Network Process (FANP) was used to identify the most influential factors that may cause stress among students during online distance learning. Five factors and twenty-one sub-factors were chosen and studied. The factors were time management, environment of study, resources, and family's as well as lecturer's concerns. The percentage value, which denoted the rank of each factor, was calculated using the FANP. Results show the environment of study was the most dominating factor, which contributed to student's stress during ODL. The findings of this research are useful for different groups of decision makers in education to plan effective strategies for the implementation of ODL.